2019
DOI: 10.1111/ejn.14338
|View full text |Cite
|
Sign up to set email alerts
|

The role of aquaporin‐4 and transient receptor potential vaniloid isoform 4 channels in the development of cytotoxic edema and associated extracellular diffusion parameter changes

Abstract: The proper function of the nervous system is dependent on the balance of ions and water between the intracellular and extracellular space (ECS). It has been suggested that the interaction of aquaporin‐4 (AQP4) and the transient receptor potential vaniloid isoform 4 (TRPV4) channels play a role in water balance and cell volume regulation, and indirectly, of the ECS volume. Using the real‐time iontophoretic method, we studied the changes of the ECS diffusion parameters: ECS volume fraction α (α = ECS volume frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 71 publications
4
25
1
Order By: Relevance
“…Another possibility is adenosine, acting via A2A receptors, which induces branch retraction during inflammatory states but has less effect on ramified microglia in the healthy brain (Orr, Orr, Li, Gross, & Traynelis, 2009). In any case, our data suggest that inhibition of retinal TRPV4 channels profoundly affects microglial morphology, potentially impeding the transition towards proinflammatory‐like phenotypes in tissues exposed to hypotonic gradients (e.g., Chmelova et al, 2019; Gankam‐Kengne et al, 2010). The precise molecular mechanisms that mediate volume‐dependent process remodeling should be established in microglia‐specific mouse knockout lines.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Another possibility is adenosine, acting via A2A receptors, which induces branch retraction during inflammatory states but has less effect on ramified microglia in the healthy brain (Orr, Orr, Li, Gross, & Traynelis, 2009). In any case, our data suggest that inhibition of retinal TRPV4 channels profoundly affects microglial morphology, potentially impeding the transition towards proinflammatory‐like phenotypes in tissues exposed to hypotonic gradients (e.g., Chmelova et al, 2019; Gankam‐Kengne et al, 2010). The precise molecular mechanisms that mediate volume‐dependent process remodeling should be established in microglia‐specific mouse knockout lines.…”
Section: Discussionmentioning
confidence: 77%
“…Identified by its ability to transduce hypotonic stimuli (HTS) in recombinant cells (Strotmann, Harteneck, Nunnenmacher, Schultz, & Plant, 2000), TRPV4 was shown to regulate cell swelling in many cell types, including some macroglia (Becker, Blasé, Bereiter‐Hahn, & Jendrach, 2005; Hoshi et al, 2018; Jo et al, 2015; Lee, Stowers, & Chaudhuri, 2019, but see Chmelova et al, 2019). We investigated the dynamics of microglial volume regulation by exposing eGFP + cells to HTS while keeping the external solution's ionic strength constant (Jo et al, 2015; Ryskamp et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…AQP4 and TRPV4 function is linked to osmosensing and the adaptation to extracellular osmolality of astrocytes (Benfenati et al, 2011a;Jo et al, 2015;Mola et al, 2016;Chmelova et al, 2019), and results described here also indicate there may be similar mechanisms employed by NP cells.…”
Section: Ca 2+ Influx In Response To Extracellular Osmotic Shiftssupporting
confidence: 59%
“…Indeed, in the present study, the expression of several ion channels, such as TRPV4, NKCC1 and Na + /K + ‐ATPase α2, significantly decreased in the immobilized skeletal muscles. Moreover, osmotic homeostasis and cell volume were respectively regulated by functional interaction between AQP4 and these ion channels (Chmelova et al, 2019; Illarionova et al, 2010; Jo et al, 2015; Mola et al, 2016; Strohschein et al, 2011; Yan et al, 2018; Zhang et al, 2016). Therefore, the present study suggested that water and ion transport may decrease due to the lower expression of AQP4 and related ion channels in the immobilized skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%